KATEKESE YANG HIDUP DALAM SEMANGAT GEREJA SINODAL DI TENGAH SITUASI GEREJA DIASPORA - Liria Tjahaja (CREDENDUM: Jurnal Pendidikan Agama, 2026)
This study aims to identify the catechetical strategies that need to be developed in order to realize a kerygmatic and missionary synodal Church within the lives of the faithful, particularly in the context of a diaspora Church and contemporary evangelization challenges. The methodology employed in this paper is library research, gathering data from relevant ecclesiastical documents, books, and journal articles, which are subsequently analyzed qualitatively using descriptive analysis techniques. The findings of this study demonstrate that to address contemporary evangelization challenges and the context of the diaspora Church, the necessary catechetical strategies to be developed entail revitalizing basic Christian communities (Kelompok Basis Gerejawi) and developing digital community catechesis, particularly for the faithful who face geographical and temporal constraints in gathering physically.